Effect of ultrasound and ethanolic extract of oil palm fronds on the quality characteristics of marinated goat meat - P., Kumar; Mohd Sobri, R. A.; Mohammad Fuad, N. H.; Adewale, M.A.; Rahman, M.M.; M. R., Ismail Fitry; Sazili, A.Q. (Indian Society for Sheep and Goat Production Utilization, 2023)
A study was conducted to evaluate the effect of ultrasound and incorporation of ethanolic extract of oil palm fronds (OPF) on the quality attributes of marinated goat meat. The goat meat was marinated by applying ultrasound treatment (280 W power, 37 kHz frequency, 45 min below 10°C) and ethanolic OPF was extracted at 0.50% and 4 different treatments viz., C (Control: marinade without extract and ultrasonication), T1 (marinade with 0.5% OPF extract and no ultrasonication), T2 (marinade with ultrasonication) and T3 (marinade with 0.5% OPF extract and ultrasonication) were formed. The samples were analysed for various quality characteristics on day 0 (immediately after 45 min), day 1 and day 3 upon storage under refrigerated conditions (4±1°C). Ultrasound application significantly (P<0.05) increased the marinade pickup. The shear force value significantly (P<0.05) decreased upon ultrasound application. Ultrasound treatment resulted in increased (P<0.05) cooking loss in T2 and T3 samples as compared to C and T1. The extract incorporation resulted in improved lightness (L*) value. Ultrasound and extract incorporation were observed to improve the appearance, flavour and tenderness of goat meat. Thus, ultrasound application for 45 min with 0.5% OPF extract in the marinade improved the quality characteristics of marinated goat meat.